KONFLIK AGRARIA DAN PELEPASAN TANAH ULAYAT (STUDI KASUS PADA MASYARAKAT SUKU MELAYU DI KESATUAN PEMANGKUAN HUTAN DHARMASRAYA, SUMATERA BARAT) - Abdul Mutolib; Yonariza Yonariza; Mahdi Mahdi; Hanung Ismono (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
The conflict of forest management in Indonesia is increasing. Forest management conflicts often caused by legal pluralism between government and society. This study aims to describe the land conflicts between Melayu tribe community with government and communal land release process in Melayu tribe in Dharmasraya Forest Management Unit ( MU). Research method Production PF was using descriptive qualitative. The study was conducted in FMU in Nagari Bonjol, Koto Besar Dharmasraya Regency. results showed that 1) Agrarian conflict in FMU Dharmasraya between community and the government occured due to the recognition of legal pluralism in the forest, and 2) Communal land release occured through the buying and selling which controlled by Datuak process of are customary authorities. Evidence of trading activities the issuance of